Effect of Clinical History on Interpretation of Computed Tomography for Acute Stroke. (July 2019) - Hung, Peter; Finn, Caitlin; Chen, Monica; Knight-Greenfield, Ashley; Baradaran, Hediyeh; Patel, Praneil; Díaz, Iván; Kamel, Hooman; Gupta, Ajay
Objective: We assessed whether providing detailed clinical information alongside computed tomography (CT) images improves their interpretation for acute stroke. Methods: Using the prospective Cornell AcutE Stroke Academic Registry, we randomly selected 100 patients who underwent noncontrast head CT within 6 hours of transient ischemic attack or minor acute ischemic stroke and underwent magnetic resonance imaging (MRI) within 6 hours of the CT. Three radiologist investigators evaluated each of the 100 CT studies twice, once with and once without accompanying information on medical history, signs, and symptoms. In random sequence, each study was interpreted in one condition (ie, with or without detailed accompanying information) and then after a 4-week washout period, in the opposite condition. Using MRI diffusion-weighted imaging (DWI) as the reference standard, we classified CT interpretations as correct (true positives or negatives) or incorrect (false positives or negatives). We used logistic regression with sandwich estimators to compare the proportion of correct interpretations. Results: In patients with DWI-defined infarcts, acute ischemia was called on 20% of CTs with detailed history and 18% without history. In patients without infarcts, the absence of ischemia was called on 77% of CTs with history and 77% without history. The proportion of correct interpretations of CTs accompanied by detailed clinical history (49%) did not differ significantly from those without history (47%; odds ratio: 1.1; 95% confidence interval: 0.8-1.4). Conclusions: Reported findings on head CT for evaluation of suspected acute ischemic stroke were similar regardless of whether detailed clinical history was provided.